Voice-based Human-Machine Interaction Modeling for Automated Information Services - Maskeliunas, R.; Ratkevicius, K.; Rudzionis, V. (Elektronika ir Elektrotechnika, 2011)
Voice based human-machine dialogs are becoming more and more important part of informative services. The implementation of voice dialogs enables to realize some of the aims of telecommunication services more successfully and efficiently. The main aim is to enable the communication according the principle "anytime-anywhere". The importance of voice dialogs is also caused by the fact that principle "anytime-anywhere" often could be realized only using mobile and portable devices. Those devices typically have small keyboards and screens and hence voice based interface has advantages over traditional keyboard and screen based interface. The paper presents the model of multimodal interface which core element is the recognition of voice commands. The model targets the informative services provided by the Lithuanian medical and social security enterprises. Paper shows that recognition accuracy of Lithuanian voice commands could be increased significantly if the foreign language which has closer to Lithuanian phonetic structure engine is adapted. Ill. 2, bibl. 11, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.300